Evaluating Cumulative Drought Effect on Global Vegetation Photosynthesis Using Numerous GPP Products - Wu, Changlin; Wang, Tengjun (Frontiers in Environmental Science, 2022)
The increasing trend in drought events under the background of global warming makes it more important to understand the drought effect on vegetation photosynthesis. While diverse global gross primary production (GPP) datasets were adopted to investigate drought impact on photosynthesis, few studies focused on the discrepancies of drought response among different GPP datasets, especially for the cumulative drought impact. Therefore, a total of twenty-six global GPP datasets based on process, machine learning (ML), and light use efficiency (LUE) model schemes were obtained to appraise the cumulative impact of drought stress on photosynthesis from 2001 to 2010. Meanwhile, a relatively reliable global pattern of drought’s cumulative effect on vegetation photosynthesis was acquired from these global GPP products through probability analysis. Results illustrated that the cumulative impact of drought existed in 52.11% of vegetation cover land with the cumulative time scales dominantly at a short term (1 – 4 months, 31.81%). Obvious heterogeneity of drought cumulative effect in space and different vegetation functional types was observed, as the reliability of drought effect decreased with latitude decreasing and a higher sensitivity to drought in herbaceous vegetation than woody plants. Our findings highlighted the importance of ways in characterizing moisture conditions across vegetation types among various GPP models and the necessity of GPP dataset selection in investigating drought effect on photosynthesis.